Identyfikacja (tożsamość) wizualna państwa polskiego okiem projektanta - Włoszczyński, Andrzej-Ludwik (Instytut Sztuk Pięknych Uniwersytetu Rzeszowskiego, 2019)
The author presents successive visual changes of the national emblem of the Republic of Poland in the past hundred years, i. e. since regaining independence until now, from the perspective of a professional visual identification designer. He shows how successive experiments with form, changes and modifications of the visual aspect of Poland’s national symbols in the past 100 years have suffered from a major fault – hasty political decisions. Despite long discussions and stipulations by historians and heraldists, indeed, often against them, the decisions made have been flawed, admitting incomplete solutions, from the first attempts to regulate provisional national symbols (pursuant to the Law of 1 August 1919, where the attachment is missing containing the model of the national emblem of the Republic of Poland), to the White Eagle introduced by decree, designed by Zygmunt Kamiński (1927) and contemporary regulations. The author also presents current grass-roots attempts to address the anti-heraldic nature and incongruity of the Polish emblem as regards contemporary requirements of its implementation on various carriers of information and in various technologies.
Visual identity of the Polish state in the eyes of a designer
Keywords: Orzeł Biały; godło; identyfikacja wizualna państwa; Rzeczpospolita Polska; Zygmunt Kamiński; symbolika narodowa; White Eagle; national emblem; visual identity of the state; Republic of Poland; national symbols